Odpowiedzi

  • Doli
  • Rozwiązujący
2009-05-19T11:01:37+02:00
  • Użytkownik Zadane
2009-05-19T11:12:54+02:00
Sin²38° + sin ²52° cos²52°+ sin ²52° 1
----------------------------- = --------------------------- = --------- =
tg20°* tg40°*tg50°*tg70° tg40°*tg50°* tg20°*tg70° 1*1

1
-- = 1
1
2009-05-19T11:16:03+02:00
Sin²38°+sin²52°=>
sin²38°+1-cos²52°=>
(1-cos76°)/2+1-(1+cos104°)/2=> //*2
1-cos76°+2-1-cos104°=> //*(-1)
-3+cos76°+cos104°=>
-3+2cos(76+104/2)*((cos76-104)/2=0
-3+cos90⁰cos(-28*)=> cos90*=0 więc
nasze równanie = -3